امام احمد رضا خان کی منظوم سیرت میں جسمانی معجزات کا تحقیقی مطالعہ: "AN ANALYTICAL STUDY OF THE PHYSICAL MIRACLES IN IMAM AHMED RAZA KHAN’S POETIC SEERAH" (Al-Aasar, 2025)
This study explores the depiction of the physical miracles of the Prophet Muhammad ﷺ in the poetic biography authored by Imam Ahmed Raza Khan (1856–1921), particularly in his celebrated work Hadaiq-e-Bakhshish. Imam Ahmed Raza Khan, a prominent Islamic scholar, jurist, and poet of South Asia, employed the medium of devotional poetry to highlight the miraculous aspects of the Prophet’s life, not merely as narratives of extraordinary events but as theological affirmations of prophethood. Through a close textual analysis, this research examines how Imam Ahmed Raza poetically portrays miracles such as the flowing of water from the Prophet’s blessed fingers, the speech of inanimate objects, the healing of the sick, and the obedience of natural elements. These depictions are not only framed as historical testimonies drawn from classical sources of hadith and seerah, but also as literary devices to inspire faith, devotion, and reverence among the Muslim community.The research further reveals that Imam Ahmed Raza’s poetic discourse on miracles synthesizes theological precision with artistic eloquence. By presenting miracles in measured rhythm and metaphorical richness, he constructs an image of the Prophet ﷺ that transcends ordinary perception and firmly situates him as the “Mercy to the Worlds.” The study concludes that such poetic renderings serve both didactic and devotional functions: they reaffirm belief in the supernatural attributes granted by God to His Messenger while simultaneously cultivating love and spiritual attachment in the hearts of believers.